SISTEM INFORMASI AKUNTANSI PROYEK PADA JASA KONTRAKTOR CV. INDAH KIAT KONTRUKSI KAB TEGAL - Aang Alim Murtopo (Indonesian Journal of Informatics and Research, 2021)
The construction sector is one sector that strongly supports national development. The benefits of construction services are greatly felt by the community, for example the construction of school buildings, repair and improvement of irrigation networks, construction of hospitals and health centers, telecommunications facilities, roads, railways and so on. Development in each field will provide a very large contribution to its users. Where on CV. Indah Kiat Construction, starting from the project implementation process which takes a long time, is not fast and precise in calculating the budget plan. The purpose of this study to facilitate CV. Indah Construction Tips in calculating the RAB (Expense Budget Plan) so that it is fast and precise. Data collection methods in the form of literature studies, interviews, and observations with the SDLC system development method. The system developed includes project data, work data, price analysis data, RAB data and RAB reports. The result of this research is a project accounting information system design that makes it easier for CV. Indah Construction Tips in calculating RAB (Expense Budget Plan) quickly and accurately.